A Review Paper on Biodegradable Tableware Using Sugarcane Bagasse - Nakkeeran, S. (International Journal of Psychosocial Rehabilitation, 2019)
Biodegradable tableware offers alternatives to plastic tableware. We are on mission to phase out the uses of plastic disposal by offering alternative made from natural materials we wish to replace the plastic disposable with compostable options. When talking about sustainable natural tableware there are few terms that reoccur renewable resources, biodegradable and composite.